Assessment Knowledge of the patients’ with acute renal failure concerning dietary pattern in dialysis unite of AL-Zahraa Teaching Hospital at AL-Kut city (Medico Legal Update, 2021)
Objectives: To assess the knowledge of patients with acute renal failure concerning dietary pattern forkidney failure in dialysis unite in AL-Zahraa Teaching Hospital at AL-Kut City and Find out relationshipbetween demographic data and knowledge of patient with acute kidney failure. By a non- probability sampleaccount of (30) subjects is selected for the purpose of the present study. A questionnaire as aincomes fordata gathering, it consist of two parts; include demographic data and knowledge of patients with acuterenal failure concerning dietary pattern which composed of (18) items. By self-administration, data arecollected from those who patients with renal failure come in dialysis unite in AL-Zahraa Teaching Hospitaland analyzed through the used descriptive and inferential statistic approach. The study results indicatedthat the most of the participants are within married (60%), and most of them are male. In regarding levelof education, they most of them formally graduation, and administrative patients, as well the subjects havechronic disease such as diabetes mellitus and find statistical high significant between level of education andknowledge of patient at p-value